Improvement on strength properties of mahang wood - Khazanah Mohd Wi (2017)
This research emphasized the Improvement on Strength Properties of Mahang wood. Currently, the demand on the alternative wood has increased. Mahang wood is a light hard wood and it is a fast growing plant. The objectives of this research were to study the strength properties of Mahang wood and to study the improvement on the strength properties of Mahang wood through lamination process. The strength properties studied were regarding the different ages of wood, young at four years old and atured at eight years old. The samples were air dried for thirty days. The moisture content od samples was standardized at twelve percent. The samples were ran under Universal Testing Machine (UTM) for bending and compression test. The result showed that matured Mahang wood was stronger than young wood. It also showed that laminated form of Mahang wood was stronger than natural form. The result was analysed using S Plus Program for Analysis of Variance (ANOVA) and Correlation Analysis. In a conclusion, the objectives of this research was successfully met and Mahang wood could be recommended as an alternative in wood industry.